2022
DOI: 10.1371/journal.pdig.0000164
|View full text |Cite
|
Sign up to set email alerts
|

Governing partnerships with technology companies as part of the COVID-19 response in Canada: A qualitative case study

Abstract: Cross-sector partnerships are vital for maintaining resilient health systems; however, few studies have sought to empirically assess the barriers and enablers of effective and responsible partnerships during public health emergencies. Through a qualitative, multiple case study, we analyzed 210 documents and conducted 26 interviews with stakeholders in three real-world partnerships between Canadian health organizations and private technology startups during the COVID-19 pandemic. The three partnerships involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A review of technology sector-led initiatives to address digital health equity [ 70 ] identified several programs to support access to education, transportation, housing and other supports. There is great potential for these types of programs, when conducted ethically and with transparency [ 71 ], to have a real impact for access to DMH technologies by providing targeted supports to equity-deserving populations.…”
Section: Discussionmentioning
confidence: 99%
“…A review of technology sector-led initiatives to address digital health equity [ 70 ] identified several programs to support access to education, transportation, housing and other supports. There is great potential for these types of programs, when conducted ethically and with transparency [ 71 ], to have a real impact for access to DMH technologies by providing targeted supports to equity-deserving populations.…”
Section: Discussionmentioning
confidence: 99%